DAMPAK PENURUNAN HARGA KARET TERHADAP ALOKASI TENAGA KERJA DAN PENGGUNAAN PUPUK DI KABUPATEN OGAN ILIR PROVINSI SUMATERA SELATAN - Herleni, Evi; Huanza, Muhammad (AGRIPITA JOURNAL, 2017)
The purposes of this research were to : 1) Analyze the use of family labor differences before and after the fall in prices, 2) Analyzing differences in the use of fertilizer before and after the fall in prices, 3) Analyzing the rubber farm income difference before and after the fall in prices. This study was conducted in Ogan Ilir, South Sumatra Province to take the District Payaraman, and subsequently taken Payaraman village and the village of Lubuk Bandung as a sample. The choice of location research done intentionally (purposive) on the basis that this location is predominantly doing rubber farming as the main source of livelihood besides rubber farmers in the village of Lubuk Bandung Payaraman and active program of plantation activities. The data was collected in February to April 2016. The sampling method used in this research is the method of Random Sampling Layered Not Balanced (disproportionate stratified sampling) with the number of respondents was 60 sample, consist of 30 villages and 30 villages have not advanced forward. The result of this research showed that The allocation of labor in the family farmer in rubber tapping activities, cleaning the garden and fertilization on average/th in the village Payaraman and in the village of Lubuk Bandung before the fall in prices in the amount of 486.4 HOK/th and after the fall in prices is equal to 423.43 HOK/th. Total use of fertilizer before the fall in prices in the village Payaraman and in the village of Lubuk Bandung which amounted to 43.810 lg/th while expanding arable after the fall in prices in the amount of 15.550 lg/th. The average value of the rubber farmers use fertilizer before the fall in prices is Rp. 1.80165 lg/th and after the fall in prices is Rp. 702.600 lg/th. Rubber farmers' income before the fall in prices in the village Payaraman and in the village of Lubuk Bandung is Rp. 69,303,761 lg/th and income after the fall in prices is Rp. 21,300,341 lg/th.